Mewujudkan Generasi Melek Politik Melalui Pendidikan Kewarganegaraan Dalam Menyongsong Indonesia Emas 2045 - Nassa, Daud Yefkanius (PGSD Universitas Muria Kudus, 2024)
This study aims to analyze the role of civic education in enhancing political awareness and active engagement among young people. The research employs a qualitative approach, utilizing literature review and document analysis methods. Data collection techniques involve reviewing academic articles, policy reports, and existing civic education program documents. Research instruments include document analysis sheets to evaluate curriculum content, teaching materials, and instructional methods. The data were analyzed using thematic analysis to identify patterns and relationships relevant to youth political awareness.The findings indicate that civic education has a positive impact on increasing political awareness among youth. Interactive and contextual programs, such as simulations, discussions, and participation in local and national political activities, have proven more effective in improving political literacy. However, the study also highlights challenges, including limited resources and curricula that are less aligned with current socio-political realities. Recommendations include curriculum improvements, educator training, and increased access to educational resources. These efforts require collaboration between educational institutions, the government, and the community to ensure that civic education can adequately prepare the younger generation to face future challenges and contribute positively to Indonesia’s Golden Era.